Escort Husimi distributions, Fisher information and nonextensivity - Pennini, Flavia (2004)
We evaluate generalized information measures constructed with Husimi distributions and connect them with the Wehrl entropy, on the one hand, and with thermal uncertainty relations, on the other one. The concept of escort distribution plays a central role in such a study. A new interpretation concerning the meaning of the nonextensivity index q is thereby provided. A physical lower bound for q is also established, together with a “state equation” for q that transforms the escort-Cramer–Rao bound into a thermal uncertainty relation.